2003
DOI: 10.1139/b03-097
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the developmental regulation of the cyanogenic compounds in seedlings of two lines ofLinum usitatissimumL.

Abstract: The developmental profiles and tissue distribution of the four cyanogenic compounds in seedlings of two developmentally contrasting inbred lines of flax (Linum usitatissimum L.) were examined using HPLC. During germination, the isoleucine-derived compound, neolinustatin, was hydrolysed faster in the more vigorous of the two lines. Furthermore, in this line, the neolinustatin content was higher in seeds and the accumulation of the other isoleucine-derived compound, lotaustralin, was also higher in the cotyledon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…It was also known from earlier work, however, that cyanogenic monoglucosides 4 and 5 undergo further glucosylation to form 6 and 7 as the capsules progress to maturity, 39 with the diglucosides herein found to be spatially distributed specifically in flax seed endosperm and embryo tissues by 6−7 DAF (Figures 4I,J). These MALDI imaging findings are thus in agreement with previous reports that cyanogenic glucoside contents in flax tissues vary with age and developmental stage, 22,23,35,41 with the mature embryo specifically being where cyanogenic diglucosides storage occurs.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…It was also known from earlier work, however, that cyanogenic monoglucosides 4 and 5 undergo further glucosylation to form 6 and 7 as the capsules progress to maturity, 39 with the diglucosides herein found to be spatially distributed specifically in flax seed endosperm and embryo tissues by 6−7 DAF (Figures 4I,J). These MALDI imaging findings are thus in agreement with previous reports that cyanogenic glucoside contents in flax tissues vary with age and developmental stage, 22,23,35,41 with the mature embryo specifically being where cyanogenic diglucosides storage occurs.…”
supporting
confidence: 92%
“…39,40 These diglucosides are then considered to be stored as such in unaltered form until the seed enters the germination phase, where they are reportedly hydrolyzed back to monoglucosides or completely hydrolyzed without accumulation of monoglucosides forming acetone cyanohydrin, which dissociates into acetone and HCN. 22,35,39 Subsequently, the HCN is recycled to asparagine by βcyanoalanine synthase. 39,42 This storage mechanism thus suggests a potential role of cyanogenic compounds as Nstorage compounds that could be later used for amino acid synthesis during germination.…”
mentioning
confidence: 99%
“…It is believed that by hydrolysis of CNGs during seed germination, they are thought to be used as a nitrogen source for amino acid synthesis and, at the same time, the released hydrogen cyanide (HCN) performs a protective function of germs against pests (Krech and Fieldes, 2003). The process of cyanogenesis leads to serious problems for feeding animals while cyanogenic glycosides as defensive secondary metabolites play important roles in plant development and response to adverse environment (Pičmanová et al, 2015).…”
Section: Cng As Part Of Plant Defense Mechanismmentioning
confidence: 99%
“…These enzymes should show NADP oxidoreductase activity. In addition, it has been shown that despite the fact that linustatin and linamarin are synthesized from valine and neolinustatin, and lotaustralin are formed from isoleucine, the synthesis of these compounds is under the control of one enzyme complex [ 13 ]. A gene encoding linamarase (LIN)—the enzyme responsible for converting diglucosides to cyanogenic monoglycosides—was identified in a similar way.…”
Section: Resultsmentioning
confidence: 99%